Predictors of pregnancy-associated venous thromboembolism: A case-control study - Alsheef, Mohammed A.; Alabbad, Alhanouf M.; Albassam, Rowida A.; Alarfaj, Rawan M.; Zaidi, Abdul Rehman Zia; Alarfaj, Ouhod A.; Ayyash, Mohsen; Abu-Shaheen, Amani (Frontiers in Cardiovascular Medicine, 2022)
Background: Venous thromboembolism (VTE), manifesting as pulmonary embolism (PE) or deep vein thrombosis (DVT), is the most common cause of morbidity and death during pregnancy and the postpartum period. We conducted this study to describe the predictors of pregnancy-associated VTE (DVT and PE). Methods: A case-control study was conducted at a tertiary care center in Riyadh. A total of 380 patients were included in this study, 180 of whom were diagnosed with pregnancy-associated thrombosis and 200 of them showed no VTE. Demographic data and data on risk factors of VTE were collected by reviewing the medical charts and the risk assessment tool of the Royal College of Obstetricians and Gynecologists, respectively. The main outcome measures were VTE, manifesting as PE or DVT. Results: The following factors were identified as the predictors of VTE through multivariate analysis: family history (OR=50.47, 95% CI: 6.78–375.64, P-Value<.0001), thrombophilia (OR=21.99, 95% CI: 2.83–170.63, P-Value=.003), and presence of gross varicose veins (OR=17.15, 95% CI: 3.93–74.87, P-Value<.0001). Conclusions: The findings of this study showed that family history, thrombophilia, and presence of gross varicose veins were risk factors for VTE, exceeding other transient risk factors. Hence, prophylaxis is highly recommended for those women who present with any of these factors.